Digital Transformation and Cultural Policies in Europe - Ole Marius Hylland; Jaka Primorac (Routledge, 2024)
What happens when cultural policy turns digital? Digital Transformation and Cultural Policies in Europe analyzes and compares different digital cultural policies of Europe. Through case studies of seven European countries (UK, Germany, Croatia, Sweden, Spain, Norway, and Switzerland) as well as the analysis of EU digital cultural policy, the book investigates what happens when cultural policy gets changed and challenged by digital culture. Based on a thorough discussion of key concepts and analytical perspectives, this collection also offers a unique multi-disciplinary contribution that shows how digital cultural policy is hyperconvergent. These policies contain established ideas of cultural policy – such as democratization, welfare, access, and national, protectionist ideas – brought together within a digital framework, while also adding new cultural policy tools and instruments, such as digital standards, international regulations, directives, etc. The book shows how digital cultural policies are works in progress, struggling to align their aspirations with their effectiveness. Overall, this book provides a valuable tool for understanding the current policy framework of digital culture. It will be of interest not only to scholars and students in cultural and creative industries but also to creative professionals and policy makers.
Keywords: 300; Digital Era; European Union; germany; Norway; Post-EU World; Spain; Sweden; UK